Customer Purchase Intention in a Local Fast Food Restaurant: Testing the Role of Social Media Marketing Activities - Lamhot Keegan P; Usep Suhud; Andi M Sadat (International Journal Labs, 2023)
The main aim of this study was to investigate the role of social media marketing activities on customer purchase intention in a local fast food restaurant. The independent variabel used in this study is social media marketing activities and the dependent variabel used in this study is purchase intention. The intervening variables used are value equity, brand equity, and relationship equity. Necessary data was gathered from the followers of social media via a quantitative online survey. Using a self administrated questionnaire, 250 respondents were asked to answer the survey employing convenience sampling method. After obtaining the desired responses, the data was analyzed by the AMOS 24 structural equation modeling. The results indicated that for direct effects, social media marketing activities have positive and significant effects on value equity, brand equity, and relationship equity. The results also indicated that brand equity and relationship equity have positive and significant effects on purchase intention. Value equity has positive but not significant effect on purchase intention. Then social media marketing activities have negative direct effects on purchase intention. Meanwhile, for indirect effects, social media marketing activities don’t have significant effects on purchase intention through value equity. But social media marketing activities have moderate effects on purchase intention through brand equity. Finally, social media marketing activities have significant effects on purchase intention through relationship equity.